Aprendizagem de competências no Ensino Superior: proposta de um ecossistema conectivo de invenção no paradigma da educação OnLIFE - Santos, Antonio Wilson dos (Universidade do Vale do Rio dos Sinos, 2025)
This doctoral research investigates competency-based learning in higher education for inhabiting the third millennium, aiming to propose a connective ecosystem of invention within the OnLIFE education paradigm. Situated in the broader context of competency learning in Industry 4.0 and the demands necessary for inhabiting the new millennium, the research problem is formulated through the following inquiry: How can the OnLIFE Education paradigm contribute to the co-creation of a connective ecosystem of invention that fosters competency learning in higher education? In response to this question, the general objective of the study is to understand how the OnLIFE education paradigm can contribute to the co-creation of a connective ecosystem of invention that promotes the development of competencies in higher education. From a theoretical-methodological standpoint, the study articulates competency learning, Innovation Ecosystems, the ESTREAM perspective, and OnLIFE Education. For the production and analysis of knowledge, the research employed the Cartographic ResearchIntervention Method, proposed by Passos, Kastrup, and Escóssia (2015). Throughout the knowledge-production trajectory, it included cartographic management interviews, field journals, participant observation, and photographic and audiovisual records. These data were analyzed through the Cartographic Reflexive Thematic Analysis (ATRC). The results demonstrate that competency learning transcends the technical/cognitive domain and encompasses communicational, socioemotional, reflexive/metacognitive, ethical, and socialresponsibility competencies, as well as technological, ecosystemic, and ecological thinking— fundamental for the new world of work. The Systematic Literature Review revealed still-modest international growth on the theme and a notable absence of production in South America, reinforcing the relevance of this study. ATRC analyses revealed that connective ecosystems of invention enhance learning by functioning as living laboratories, enabling interactions in transorganic connective acts that articulate curriculum, practice, and market. It was confirmed that the characteristics of OnLIFE Education—Hybridism, Multimodality, Digital Technologies as environmental forces, Inventive Learning, and Sympoiesis—are decisive for the emergence of such ecosystems. Finally, the study found that the ESTREAM model expands the conditions for pedagogical innovation by integrating science, technology, engineering, arts, and mathematics with empathy, entrepreneurship, and reflection, thereby strengthening inventive, integrated pedagogical practices guided by human, social, and epistemological values.
Keywords: Educação OnLIFE; STEAM; Indústria 4.0; Educação Superior; Cartografia; Cocriação; OnLIFE Education; ESTREAM; Industry 4.0; Higher Education; Cartography; Cocreation; ACCNPQ::Ciências Humanas::Educação